Congestive Heart Failure in Newborns (Part 2) - L.V. Kolyubakina; O.V. Vlasova; L.O. Bezrukov; O.K. Koloskova (Zaslavsky O.Yu., 2012)
The paper presents the features of pathogenesis, clinical picture, diagnosis and treatment of congestive heart failure in newborns.